Breeding for fungal resistance in Musa - Hartman, J.B.; Vuylsteke, D.R. (Springer, 1999)
Bananas and plantains are both important staple foods and cash crops for millions of people. Bananas are large perennial herbs of the genus Musa. Cultivated bananas are primarily triploids (3x) derived from intraspecific and interspecific crosses of two diploid species Musa acuminata Colla (Ma.) and Musa balbisiana Colla (M.b.) (Simmonds, 1995). In West and Central Africa, plantains provide more than 25% of the carbohydrate requirements for over 70 million people (Vuylsteke et al., 1993). In Uganda, Burundi, and Rwanda, consumption of cooking bananas exceeds 200kg per person per year. The spread of the fungal pathogen Mycosphaerella fijiensis Morelet into Africa has lead to serious declines in the productivity of banana and plantain based farming systems, and lead to the establishment of a plantain breeding program at the International Institute of Tropical Agriculture (HTA) in 1987 (Vuylsteke et al, 1993). Yield losses from fungal pathogens have been the main impetus for the establishment of banana breeding programs throughout the world (Buddenhagen, 1990).The first breeding program was established in 1922 at the Imperial College of Tropical Agriculture (ICTA) in Trinidad to produce dessert bananas resistant to Fusarium oxysporum f. sp. cubense (F. o.c.) the causal agent of Fusarium wilt or Panama disease (Simmonds, 1966). Breeding at ICTA was latter transferred to the Banana Board of Jamaica (BBJ). A second breeding program was established by United Fruit Company in Honduras to breed for resistance to yellow Sigatoka, Mycosphaerella musicola (Mm.), and Fusarium wilt and was later turned over to the Fundaciôn Hondurefia de Investigaciôn Agricola (FHIA) (Rowe, 1984).These early breeding efforts have been reviewed by others (Simmonds, 1966; Sheperd, 1974; Stover & Buddenhagen, 1986; Rowe & Rosales, 1990; Ortiz et al, 1995). The past decade has seen the release of cultivars from breeding programs at FHIA, UTA, the Centre de Coopération Internationale en Recherche Agronomique pour le Development (CERAD), the Centre Régional Bananiers et Plantains (CRBP), the Centro Nacional de Pesquisa de Mandioca Fruticultura of Empresa Brasileira de Pesquisas (CNPMF/EMBRAPA), the Institute Nacional de Investigacion Viandas Tropicales (INIVIT), and the Taiwan Banana Research Institute (TBRI). These cultivars have resistance to Fusarium wilt, black Sigatoka, or yellow Sigatoka, and many have multiple resistances (Rowe & Rosales, 1996). The methods used to produce these cultivars and the “breeding philosophies” behind them vary greatly. This paper will review the methods and philosophies of breeding for fungal resistance in Musa research, and discuss the future of new resistant banana and plantain cultivars and resistance breeding in Musa.